Waiting times for carotid endarterectomy in UK: observational study. (4th June 2009) - Halliday, Alison W; Lees, Tim; Kamugasha, Dora; Grant, Robert; Hoffman, Alex; Rothwell, Peter M; Potter, John F; Horrocks, Michael; Naylor, Ross; Rudd, Anthony G
Abstract : Objectives To assess timeliness of carotid endarterectomy services in the United Kingdom. Design Observational study with follow-up to March 2008. Setting UK hospitals performing carotid endarterectomy. Participants UK surgeons undertaking carotid endarterectomy from December 2005 to December 2007. Main outcome measures Provision and speed of delivery of appropriate assessments of patients; carotid endarterectomy and operative mortality; 30 day postoperative mortality. Results 240 (61% of those eligible) consultant surgeons took part from 102 (76%) hospitals and trusts. Of 9913 carotid endarterectomies recorded on hospital episode statistics, 5513 (56%) were included. Of the patients who underwent endarterectomy, 83% had a history of transient ischaemic attack or stroke. Of these recently symptomatic patients, 20% had their operation within two weeks of onset of symptoms and 30% waited more than 12 weeks. Operative mortality was 0.5% during the inpatient stay and 1.0% (95% confidence interval 0.7% to 1.3%) by 30 days. Conclusion Only 20% of symptomatic patients had surgery within the two week target time set by the National Institute for Health and Clinical Excellence (NICE). Although operative mortality rates are comparable with those in other countries, some patients might experience disabling or fatal stroke while waiting for surgery and hence not be included in operative statistics. Major improvements in services are necessary to enable early surgery in appropriate patients in order to prevent strokes.